Effect of Excess Metal Concentration on the Extraction Potential of Di-(2-Ethylhexyl) Phosphoric Acid: dissociation constant, di-(2-ethylhexyl) phosphoric acid, copper extraction (Biological Sciences - PJSIR, 2006)
The extraction potential of di-(2-ethylhexyl) phosphoric acid (DEHPA) in kerosene increases manyfold on loading calcium into the organic phase before equilibration with aqueous copper feed. The control of pH was unnecessary in the range from pH 5.0 to pH 3.0. It was found that copper can easily replace nickel, sodium and calcium in the organic phase because of the difference in the dissociation constants of copper and other metals studied. The hydrolysis of calcium maintains the pH of the aqueous phase in favour of higher extraction of copper by DEHPA.